Association between compound dietary antioxidant index and all-cause and cancer mortality in patients with chronic obstructive pulmonary disease: results from NHANES 1999–2018 - Li, Wenqiang; Bai, Jingshan; Ge, Yanlei; Fan, Yuting; Huang, Qian; Deng, Zhiping (Frontiers in Medicine, 2025)
ObjectiveChronic obstructive pulmonary disease (COPD) is one of the most important causes of death in the world, and its core is chronic inflammation. Antioxidants play a positive role in the onset and prognosis of chronic respiratory diseases. In maintaining human health, the composite dietary antioxidant index (CDAI) plays an important function. Therefore, the purpose of the current study was to investigate the relationship between CDAI and all-cause and cancer mortality in individuals with COPD.MethodsA prospective cohort study was conducted by investigating NHANES data between 1999–2018. The study included people who satisfied the inclusion and exclusion criteria. In this study, the association between CDAI and all-cause and cancer mortality was investigated using weighted Cox regression. The relationship between them is illustrated by drawing constrained cubic spline curves (RCS). Finally, subgroup analysis is used to further verify.ResultsThe study included 1,534 participants. CDAI was associated with COPD patients mortality, and after adjusting for multiple factors, we observed a 5% reduction in the risk of all-cause mortality (HR = 0.95, 95% CI: 0.92–0.97) was associated with a 9% lower risk of cancer mortality for each one-unit increase in CDAI (HR = 0.91, 95% CI: 0.85–0.98). After adjusting for multiple factors, high CDAI was associated with a reduced risk of mortality, with patients in the high CDAI group having 35% lower all-cause mortality than those in the low CDAI group (HR = 0.65, 95% CI: 0.50–0.85), the high CDAI group had a 61% lower risk of cancer mortality (HR = 0.39,95% CI: 0.23–0.68). Subgroup analysis and sensitivity analysis showed a consistent association between CDAI and COPD mortality.ConclusionOur study highlights the inverse association between CDAI and all-cause and cancer mortality in patients with COPD. Further prospective studies are needed to confirm the role of CDAI in mortality risk in patients with COPD.